2021
DOI: 10.1021/acsomega.0c05682
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and Green Fabrication of Carbon Dots for Cellular Imaging and Anti-Counterfeiting Applications

Abstract: Carbon dots (CDs) with plenty of favorable properties have been extensively investigated in diverse areas including bioimaging, biomedicine, sensor, energy storage, anti-counterfeiting, photocatalysis, and optoelectronic devices. Herein, a simple, rapid, and green sonochemical-assisted method for fabricating nitrogen-doped CDs has been developed. In this approach, the nitrogen-doped CDs can be obtained through irradiation by intensive ultrasonic waves from ultrasonic probes in 30 min. The achieved CDs exhibit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…At present, anticounterfeiting is an important research direction of CDs fluorescence application, which has been widely reported. We compared the effect on solvent polarity and anti-counterfeiting of CDs recently reported (Table S1), [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] and found that most CDs exhibited a red-shift in their fluorescence peaks with the increase of solvent polarity and a small Stokes shift below 110 nm. In our work, with the increase of solvent polarity, the fluorescence peak blue-shifts, and Stokes shift is as large as 260 nm.…”
Section: Chemistryselectmentioning
confidence: 99%
“…At present, anticounterfeiting is an important research direction of CDs fluorescence application, which has been widely reported. We compared the effect on solvent polarity and anti-counterfeiting of CDs recently reported (Table S1), [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] and found that most CDs exhibited a red-shift in their fluorescence peaks with the increase of solvent polarity and a small Stokes shift below 110 nm. In our work, with the increase of solvent polarity, the fluorescence peak blue-shifts, and Stokes shift is as large as 260 nm.…”
Section: Chemistryselectmentioning
confidence: 99%
“…Although the synthesis routes, properties and applications of the CDs have been systematically summarized elsewhere, there are few dedicated reviews with emphases on the synthesis routes, properties and applications of the CDs [30][31][32][33]. Hence, aiming at a distinct perspective, we will compile a general review on the recent progress of the CDs.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, counterfeiting of security documents, namely currency, certi cates, passport, pharmaceutical products have signi cantly imbalances the economic condition of the world [23][24][25] . In addition, easy accessibility of anti-counterfeiting (AC) inks and its validation for the counterfeiters are the key anxieties in this area.…”
Section: Introductionmentioning
confidence: 99%